A case study of using the He Pikinga Waiora Implementation Framework: challenges and successes in implementing a twelve-week lifestyle intervention to reduce weight in Māori men at risk of diabetes, cardiovascular disease and obesity - Oetzel, John (Int J Equity Health, 2020)
BACKGROUND: Māori men have stark health inequities around non-communicable diseases. This study describes the case of a partnership attempting to develop and implement a culturally centred intervention through a collaborative partnership to potentially address the inequities. In particular, the partnership followed a participatory, co-design approach using the He Pikinga Waiora (HPW) Implementation Framework; the study presents lessons learnt in addressing health inequities following this framework. METHODS: The partnership involved a university research team and a Māori community health provider. They engaged with other stakeholders and several cohorts of Māori men through a co-design process to adapt a 12-week lifestyle intervention. The co-design process was documented through meeting notes and interviews with partners. Two cohorts participated in separate single group pre-intervention/post-intervention designs with multi-method data collection. Key outcome measures included weight loss, self-reported health, physical activity, and nutrition. Post-intervention data collection included qualitative data. RESULTS: The co-design process resulted in a strong and engaged partnership between the university team and the provider. There were significant challenges in implementing the intervention including having two additional partner organisations dropping out of the partnership just after the initial implementation phase. However, a flexible and adaptable partnership resulted in developing two distinct lifestyle interventions run with 32 Māori men (in two different cohorts of 8 and 24). All but one in the first cohort completed the programme. The first cohort had a modest although statistically insignificant improvement in weight loss (d = 1.04) and body mass index (BMI; d = 1.08). The second cohort had a significant reduction in weight loss (d = 1.16) and BMI (d = 1.15). They also had a significant increase in health-related quality of life (d = 1.7) and self-rated health (d = 2.0). CONCLUSION: The HPW Framework appears to be well suited to advance implementation science for Indigenous communities in general and Māori in particular. The framework has promise as a policy and planning tool to evaluate and design interventions for chronic disease prevention in Indigenous communities. Despite this promise, there are structural challenges in developing and implementing interventions to address health inequities. TRIAL REGISTRATION: Retrospectively registered, Australia New Zealand Clinical Trials Registry, ACTRN12619001783112.